Prediction and analysis of strength and economic feasibility of filling materials under the influence of mix proportion and curing age - Zhang, Yueying; Liang, Huizhen; Fei, Shanshan; Zhang, Aijun; Yu, Juan; Qin, Xuebin (Frontiers in Materials, 2024)
The research aims to investigate the effects of proportion and age of maintenance on the strength and economy of filling materials, in order to provide theoretical guidance and technical support for the management of coal mined-out area. Firstly, adjustments are made to the proportioning and maintenance age of the fill materials, and experiments are conducted to explore the strength performance of materials under different proportions. Secondly, GANs is utilized to expand the dataset, and an MLP-LSTM network is constructed to predict the strength of materials experiencing different maintenance ages under various proportions. Finally, integrating practical engineering applications, an economic viability prediction analysis is conducted to examine the cost of fill materials under different proportions and maintenance ages, along with their influencing factors. The results indicate that appropriate adjustments to proportioning can effectively enhance the strength of fill materials, whereas excessively high or low proportions may lead to unstable or surplus strength. Extending the maintenance age can to some extent improve the material’s strength, but it also increases maintenance costs, necessitating a comprehensive balance in terms of economic viability. Consequently, this research offers a theoretical foundation and practical guidelines for optimizing mixture proportions and selecting appropriate curing ages, providing valuable insights for enhancing the efficiency and cost-effectiveness of coal mined-out area filling treatments.